Analysis of Attributes that Become Consumer Preferences in Choosing Indonature Table Furniture Products - Fajar Haditiya Atmaja (International Journal of Review Management Business and Entrepreneurship (RMBE), 2021)
Ud. Indonature is a company engaged in furniture, especially coffee table located on the island of Lombok, West Nusa Tenggara. Furniture made of solid wood such as Teak and Trembesi wood. In recent years there has been a decrease in the company’s turnover therefore it takes product innovation to increase sales. With the need to develop coffee table furniture products more clearly, researchers decided to conduct research on Attribute Analysis that Becomes Consumer Preferences in Choosing Indonature Table Furniture Products. This study aims to find out and analyze the combination of attributes that become consumer preferences in purchasing Indonature coffee table products and to know and analyze the most important coffee table attributes for Indonature consumers. The problem formulation in this study is, firstly, what combination of attributes are the consumer preference in buying coffee table into nature products and the second is what are the most important attributes of coffee table products for indonature consumers. The results of conjoin analysis showed that the most preferred and most important combination according to consumers is made of trembesi wood material with arch form, has a natural wood finishing and rustic design.